أثر مهارة الكتابة في تحسين الخط العربي لدى التلاميذ الناطقين بغير العربية في المراحل التعليمية الأساسية في نيجيريا : Ahmad Garba - Ahmad Garba (Universitas Negeri Malang, 2021)
The writing skill is a fourth type of language skill, and it means the ability to express what is in the conscience and thoughts through transcription, and it is a skill that requires a high idea, which is always a complex scientific because it needs continuous training and continuous practice. This study aims to shed light on the impact and importance of mastering skill in improving Arabic calligraphy among non-Arabic speaking students in the basic educational stages in Nigeria. This study includes the following; Research abstract, introduction, research methodology, definition of the basic educational stages in Nigeria, the concept of writing skill, its importance, objectives of its education, types of writing, stages of its education, the status of Arabic calligraphy in education, its teaching method, research results, suggestions, conclusion and references.